Past and Present of the Vietnam Problem (Czech Journal of International Relations, 1966)
The direct military intervention of the USA in Vietnam and the bombing of the GDR by the American air force caused the Vietnamese issue to become a world issue again. The Council of Governments is interested in its early resolution and a significant part of public opinion in the world. To the forefront of the common interest aims to restore peace in this part of the world, so that further bloodshed and the spread of war to other countries and parts of the world are prevented. Solutions however, can only be built on such a basis that is acceptable for the Vietnamese nation. A solution that is not acceptable to the Vietnamese nation can only lead to a prolongation or even to the spread of the war, because the Vietnamese after twenty-five years of fighting for independence, they are determined to fight for real independence and they have enough experience, certain strengths and friends to do that. Though the Vietnamese question became a world problem, it still remains primarily a Vietnamese one, a problem that can only be solved in accordance with the authorized national thoughts and political realities of this country.